Desenvolvimento de sistemas de geoprocessamento e tecnologia móvel aplicados à agricultura de precisão - Boemo, Daniel (2011)
Being information most important one assets for the development of several areas of knowledge in various sectors of our society and knowing that in recent years with the emergence of new technologies and data sources available for free on the Internet, and also allies this, offering a wide variety of media in a big cloud that today we all know by WEB. Will be shown two solutions that were developed for the CR system Campeiro 7, related to precision farming. One is a module of computer system in which the main function is to extract MDT's from SRTM images of 90m and ASTER images 30 m resolution, and provide data for the structuring of these models, altimetric and slope on files patterns used for GIS mainly linked to agriculture. The purpose of this tool is to facilitate the acquisition of these data and provide simpler methods to accomplish the adjustment of the models and give conditions to perform the comparison of these models with other data types, such as grain production. The other computer system was implemented with mobile technologies for the removal and processing of data related to field activities done on the spot.This system in addition to performing the collection and processing of GPS data in real time, is designed to streamline processes, running on smartphone devices, due to the fact that it possesses features of a laptop. The system was created to shorten the time between the collection, processing and analysis, and also to provide results more quickly, providing alternative methods of information processing using remote resources. It also provides trace real-time ,task done in the field, such as monitoring activities carried by a tractor or a combine using telephone services or Internet.